Investigation and analysis of the effects of geometry orientation of array antenna on directivity for wire-less communication. Issue 1 (31st December 2016) - Kazema, Twahir; Michael, Kisangiri
Abstract: Array antennas offer a wide range of opportunities in the variation of their directivity patterns through amplitude and phase control. Directivity is one of very important parameters when optimizing Antenna. This paper intends to investigate the effects of different geometries of array antenna on directivity and side lobe levels. A six by four antenna array was chosen for investigation with uniform element spacing between the elements and the results were presented for each selected geometry, Array elements of dipole and patch antenna were chosen for the investigation and analysis. An analysis of the effect of the chosen antenna array was done by investigating its response when an incident emw (electromagnetic waves) from a mobile phone impinge on the array antenna where the tapering and beam-forming techniques were used for analysis and results presented.